EFEKTIFITAS PROGRAM PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN TERHADAP PRODUKSI DAN PENDAPATAN USAHATANI PADI SAWAH DI KECAMATAN MARAWOLA KABUPATEN SIGI - Wiwi Widiastuti; Effendy Effendy; Alimudin Laapo (Agroland: Jurnal Ilmu-ilmu Pertanian, 2018)
This research aimed to analyze the effectiveness ofthe Rural Agribusiness Development Program related to the performance of farmer group association at Lebanu in Marawola Sub District, Sigi Regency. It determined the differences in production and income level of the rice farming before and after receiving fund from the Rural Agribusiness Development Program at Lebanu, Sigi. Descriptive analysis was used to identify the effectiveness of the Rural Agribusiness Development Program and comparative analysis paired t-test to examine the differences in production and income of the rice farming before and after receiving the fund. The results showed that the performance of the farmer group association at Lebanu of Marawola is actually effective with a total score of 951 out of a maximum score of 1071. It indicates that the service and distribution of the funds is successful. Meanwhile, the comparison of production after and before receiving Rural Agribusiness Development Program was found that tcounted value is 11.264 >ttabel (2.010) at α 5%. Similarly, the rice farmers income after receiving the rural agribusiness development program was found that tcounted value is 8.472 >ttabel (2.010) at α 5%. The results indicate that there is a significant and positive increase on the production and income of the rice farming after receiving the funds of the rural agribusiness development program than before receiving it.